Experiments on Decisions under Uncertainty: A Theoretical Framework - Shmaya, Eran; Yariv, Leeat (American Economic Review, 2016)
The analysis of lab data entails a joint test of the underlying theory and of subjects' conjectures regarding the experimental design itself, how subjects frame the experiment. We provide a theoretical framework for analyzing such conjectures. We use experiments of decision making under uncertainty as a case study. Absent restrictions on subjects' framing of the experiment, we show that any behavior is consistent with standard updating (“anything goes”), including those suggestive of anomalies such as overconfidence, excess belief stickiness, etc. When the experimental protocol restricts subjects' conjectures (plausibly, by generating information during the experiment), standard updating has nontrivial testable implications. (JEL C91, D11, D81, D83)